Management of Teaching and Learning byconstructivism method on doing Administration Procedure in letter arranging ability tostudent X Office Administration SMK Nasional Patiof Education - Warsiti, Indiyah (2012)
The research subject are Headmaster ( 1 person), Deputy Of School ( 1 person), Teacher of Administration Procedure ( 1 person) and teacher of office administration's competensi (3 People). Data collecting method applies in-depth interview, observation, and documentation. Validity of data applies observation assidinity, confirmability, and triangulation. Data analytical technique is done systematically start from data collecting process, reduces, presenting the data, and selective assessment of conclusion and interpretation of all information. Result of research shows that a) the Management of Teaching and Learning on doing Administration Procedure in letter arranging ability covers (1)planning, ( 2)organization, (3) implementing, and (4) controlling and evaluating. b) Factors influencing management of the study of doing Administration Procedure in SMK Nasional Pati covers (1) the initial ability level of the student, (2) student motivational level, (3) teacher motivation level to improve their ability, (4) teacher ability to design the lesson plan, (5) teacher ability to apply the metode/strategi/approach that suitable with purpose and study area, (6) teacher ability to exploit supporting facilities and media in study, (7) condition and existence of supporting facilities for infrastructure and study media, (8) coordination level between subject teacher, (9) support of subject teacher to each other, and (10) support from school leader. Keyword : Management of teaching and learning, doing Administration Procedure,letter arranging ability, by constructivism method